(untitled) (Fiep Bulletin - online, 2016)
Syndrome of Premenstrual Tension (STPM) is composed of a set of physical symptoms, psychological and behavioral disorders that present clinically during the luteal phase of the menstrual cycle. Objective: To assess the profile of women in reproductive age with STPM. Descriptive exploratory study with a quantitative approach using a questionnaire to gather data and, after inclusion and exclusion criteria, the sample consisted of 160 women, considering aspects of Resolution 196/96 of MS and opinion of the CEP. With respect to sociodemographic data, the participants were aged between 15 and 45 years, most married and student, education variable and family income around 1 to 2 minimum wages. Signs and symptoms of STPM were around 82.2%. Among the most common physical changes, the highlights were swollen and painful breasts (85.6%), cramps (85%) and headache (63.8%). In relation to emotional changes, impatience showed a frequency of 87.5%, irritability (80%), will to cry (73.1%), anger (66.9%) and anxiety (62.5%). The behavioral changes most often mentioned were hostile responding to people (61.9%) and fight with the children (55%). We identified through this study the biopsychosocial changes that alter the life of women in reproductive age, affecting personal and social life of them. It is perceived ignorance about the issue, requiring that health professionals to develop programs of care and education with a view to comprehensive care for these women and better quality of life.